2004
DOI: 10.1583/03-1173.1
|View full text |Cite
|
Sign up to set email alerts
|

Change in Aneurysm Diameter After Stent-Graft Repair of Ruptured Abdominal Aortic Aneurysms

Abstract: This study suggests that ruptured AAAs treated with stent-graft experience sac regression at a higher rate compared with electively treated AAA. The reasons for these findings remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…This theory is supported by a Canadian study that, using predictive models, demonstrated improved RAAA mortality following the introduction of an endovascular program. 56 We have also reported several Greenberg et al 8 Hinchliffe et al 9 Veith and Ohki 10 Yilmaz et al 11 Van Herzeele et al 12 Scharrer-Palmer et al 13 Resch et al 14 Lee et al 15 May et al 16 Lombardi et al 17 Arya et al 18 Gerassimidis et al 19 Larzon et al 20 Brandt et al 21 Peppelenbosch et al 22 Alsac et al 23 Hechelhammer et al 24 Vaddineni et al 25 Castelli et al 26 Dalainas et al 27 Oranen et al 28 Greco et al 29 Visser et al 30 Hinchliffe et al 31 Acosta et al 32 Peppelenbosch et al 33 Coppi et al 34 Franks et al 35 Mehta et al 36 The reported mortality rates after endovascular repair vary a great deal in the literature. Useful data can be extracted from 2 registries 56,57 and 4 meta-analyses.…”
Section: Commentmentioning
confidence: 71%
“…This theory is supported by a Canadian study that, using predictive models, demonstrated improved RAAA mortality following the introduction of an endovascular program. 56 We have also reported several Greenberg et al 8 Hinchliffe et al 9 Veith and Ohki 10 Yilmaz et al 11 Van Herzeele et al 12 Scharrer-Palmer et al 13 Resch et al 14 Lee et al 15 May et al 16 Lombardi et al 17 Arya et al 18 Gerassimidis et al 19 Larzon et al 20 Brandt et al 21 Peppelenbosch et al 22 Alsac et al 23 Hechelhammer et al 24 Vaddineni et al 25 Castelli et al 26 Dalainas et al 27 Oranen et al 28 Greco et al 29 Visser et al 30 Hinchliffe et al 31 Acosta et al 32 Peppelenbosch et al 33 Coppi et al 34 Franks et al 35 Mehta et al 36 The reported mortality rates after endovascular repair vary a great deal in the literature. Useful data can be extracted from 2 registries 56,57 and 4 meta-analyses.…”
Section: Commentmentioning
confidence: 71%
“…Patients undergoing emergency EVAR were not included in this study as they have previously been demonstrated to behave differently to elective repairs. 4,5 The morphological suitability was assessed by contrast-enhanced computed tomography (CT), and medical fitness was determined before the procedure. CT images were discussed at the weekly meeting between the radiologists and surgeons, and suitability for EVAR decided.…”
Section: Methodsmentioning
confidence: 99%
“…6,7 Other studies have suggested that ruptured aneurysms treated with EVAR experience sac regression at a higher rate than do electively treated aneurysms. 8 It is likely that other independent anatomic or physiologic variables may influence the behavior of the aneurysm sac follow-ing EVAR. 9 This study was undertaken to determine the relationship between aneurysm sac size change at 1, 6, 12, or 24 months and a set of 10 independent "predictive" variables by using a general linear model analysis.…”
mentioning
confidence: 99%